Longitudinal associations among physical activity and sitting with endocrine symptoms and quality of life in breast cancer survivors: A latent growth curve analysis - Alexander R. Lucas; Youngdeok Kim; Autumn Lanoye; R. Lee Franco; Arnethea L. Sutton; Jessica G. LaRose; Masey Ross; Vanessa B. Sheppard (Cancer Medicine, 2023)
Abstract Purpose Adjuvant endocrine therapy (AET) often causes debilitating endocrine symptoms that compromise quality of life (QOL) in women diagnosed with hormone receptor positive breast cancer (BC). We examined whether greater levels of physical activity (PA) or prolonged sitting were associated with reduced side effects or worse side effects of AET, respectively. Methods We used parallel process latent growth curve models to examine longitudinal patterns in PA and sitting behaviors, and their association with endocrine symptoms and QOL over 3 years of follow‐up in 554 female BC survivors undergoing AET. Results At baseline, women were a mean age of 59 years, mostly white (72%), with overweight/obesity (67%), and approximately 50% were within 1 year of diagnosis. Unconditional models showed significant increases in PA (p < 0.01) over time but no change in sitting. Endocrine symptoms, general and BC‐specific QOL all significantly worsened over time (p < 0.01). Parallel process models showed no cross‐sectional or longitudinal associations between PA and endocrine symptoms. Higher levels of baseline PA were associated with higher baseline QOL scores (p = 0.01) but changes in PA were not associated with changes in QOL. Conversely, more sitting at baseline was associated with worse endocrine symptoms, general and BC specific QOL (ps <0.01). At baseline, having better QOL scores was associated with increases in sitting (ps <0.01), while having worse endocrine symptoms was associated with a slower rate of increase in sitting (p < 0.01). Increases in sitting time were also associated with a slower rate of increase in endocrine symptoms (p = 0.017). Model fit statistics (x2, CFI, TLI, SRMR) were acceptable. Conclusion Both PA and sitting behaviors are important for the management of symptoms and in maintaining QOL in BC survivors. Women with already high symptom burden do not increase sitting time further but having better general and BC specific QOL to begin with means a greater decline over time.